Isothermal Amplification and Multimerization of DNA by Bst DNA Polymerase. (April 2001) - Hafner, G.J.; Yang, I.C.; Wolter, L.C.; Stafford, M.R.; Giffard, P.M.
We have demonstrated the isothermal in vitro amplification and multimerization of several different linear DNA targets using only two primers and the strongly strand-displacing exonuclease-negative Bst DNA polymerase. This reaction has been termed linear target isothermal multimerization and amplification (LIMA). LIMA has been compared with cascade rolling-circle amplification and has been found to be less sensitive but to yield similar variable-length multimeric dsDNA molecules. Products from several different LIMA reactions were characterized by restriction analysis and partial sequence determination. They were found to be multimers of subsets of the target sequence and were not purely primer derived. The sensitivities with respect to target concentration of several different LIMA reactions were determined, and they varied from 0.01 amol to 1 fmol. The sensitivity and specificity of LIMA were further tested using E. coli genomic DNA, and the selective amplification of a transposon fragment was demonstrated. A successful strategy for reducing LIMA-dependent background DNA synthesis in rolling-circle amplification embodiments was devised. This entailed the affinity purification of circular DNA templates before amplification.